PERIODS OF MOTION IN PERIODIC ORBITS IN THE EQUATORIAL PLANE OF AMAGNETIC DIPOLE - JUAREZ (UNIVERSIDAD NACIONAL AUTONOMA DE MEXICO, INSTITUTO DE FISICA, CD. MEXICO, DF, MEX, 1950)
The differential equations of motion of an electrically charged particle in the equatorial plane of a magnetic dipole are solved in a way that time appears directly. The period of motion for periodic orbits is then found, and an application to cosmic radi
PHYS REV D
Keywords: PERIODS, MOTION, PERIODIC ORBITS, EQUATORIAL PLANE, AMAGNETIC DIPOLE; MULTIDISCIPLINARIA; ELECTROMAGNETISMO; MAGNETISMO